HRM System and Intra-Organizational Trust as a Factors Generating Positive Attitudes and Behaviour of Employees in Public Sector Organisations - Lewicka , Dagmara (Studia Oeconomica Posnaniensia, 2016)
The aim of the study was to identify the relationship between HRM systems and intra-organizational trust and the level of job satisfaction. Moreover, the impact of these variables are valuable for organizing employee behaviour, such as showing a pro-innovative attitude, helping others, and low turnover intention. The study was conducted on a group of 134 randomly selected employees of public sector organizations. Multiple linear regression analysis also identified the probable relationships between variables, showing among others the relationship between job satisfaction and HRM system and the level of intra-organizational trust.